Assessment of Change and the Reasons of Development of the Level of Financial Self-Sufficiency of Towns with County Rights in Poland - Kozera , Agnieszka; Standar , Aldona (Studia Oeconomica Posnaniensia, 2018)
The aim of the article was to analyse the level of financial self-sufficiency of towns with county rights in Poland in the years 2007-2014. In the first step of the research the level and the share of own income in the total income of towns with county rights on the background of other entities of the local government sector in Poland were presented. Then, in the second step of the research Ward's method was used to identify the classes of the typological level of self-sufficiency of towns with county rights.